Kerjasama Sister City Kota Semarang dengan Kota Brisbane Australia - Rosida, Fatma; Hartati, Anna Yulia (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2023)
The Afghan conflict which has not found a bright spot for peace between the Afghan government and the Taliban group has involved superpower countries such as the United States. The Taliban group that wants to implement radicalism is ultimately seen as a serious problem, both at the regional and international levels. The Indonesian government made a policy to continue to help Afghanistan achieve peace. Indonesia and Afghanistan that have something in common include common ideas, common goals, common causes of conflict, shared vision, and the characteristics of a Muslim population. Afghanistan has an interest in studying Indonesian soft power policies and concepts in conflict resolution. This study uses a soft power diplomacy currency framework that can explain Indonesia's diplomacy in conflict resolution. The qualitative method in this study uses secondary data obtained from the study literature. Thus, this study shows that the practice of Indonesian diplomacy in assisting the Afghan peace process is in accordance with the soft power currency approach which consists of three concepts, namely benignity, brilliance, and beauty.